Phenothiazine-benzimidazole architecture as an efficient interfacial charge transport layer for perovskite blue light emitting diodes - Sonigara, KK; Wang, H; Chao, J; Xie, Z; Fan, J; Huang, J; Stavrinou, PN; Bradley, DDC (SPIE, 2021)
Solution-processed metal halide perovskite light-emitting diodes (Pe-LEDs) show great promise in a range of optoelectronic applications. However, these devices can be limited by poor interfaces to the perovskite films due to poor crystallization control during film processing caused by de-wetting from the bottom layer. The deep (Highest Occupied Molecular Orbital) HOMO levels of the emitters also lead to large charge injection barriers for standard electrodes. To improve this, we develop and report on a small molecule, BPS2, based on phenothiazine-benzimidazole with Lewis base sites. This promising interfacial material is then applied to blue PeLEDs where the energy band alignment of BPS2 to the blue perovskite emitter helps to reduce the hole-injection barrier while blocking electrons. BPS2 can be solution-processed with non-chlorinated organic solvents and provides improved wettability towards perovskite precursor solutions compared to conventional PEDOT:PSS hole transport films. A thin interlayer of BPS2 introduced between PEDOT:PSS and a perovskite emission layer is shown to improve both the device external quantum efficiency and luminance in comparison to the reference device without the interlayer.